Serum and macular response to carotenoid-enriched egg supplementation in human subjects: the Egg Xanthophyll Intervention clinical Trial (EXIT) - Kelly, David; Nolan, John M.; Howard, Alan N.; Stack, Jim; Akuffo, Kwadwo O.; Moran, Rachel; Thurnham, David I.; Dennison, Jessica; Meagher, Katherine A.; Beatty, Stephen (British journal of nutrition, 2017)
The macular carotenoids lutein (L), zeaxanthin (Z) and meso-zeaxanthin (MZ) accumulate at the macula, where they are collectively referred to as macular pigment (MP). Augmentation of this pigment, typically achieved through diet and supplementation, enhances visual function and protects against progression of age-related macular degeneration. However, it is known that eggs are a rich dietary source of L and Z, in a highly bioavailable matrix. In this single-blind placebo-controlled study, L- and MZ-enriched eggs and control non-enriched eggs were fed to human subjects (mean age 41 and 35 years, respectively) over an 8-week period, and outcome measures included MP, visual function and serum concentrations of carotenoids and cholesterol. Serum carotenoid concentrations increased significantly in control and enriched egg groups, but to a significantly greater extent in the enriched egg group (P<0·001 for L, Z and MZ). There was no significant increase in MP in either study group post intervention, and we saw no significant improvement in visual performance in either group. Total cholesterol increased significantly in each group, but it did not exceed the upper limit of the normative range (6·5 mmol/l). Therefore, carotenoid-enriched eggs may represent an effective dietary source of L, Z and MZ, reflected in significantly raised serum concentrations of these carotenoids, and consequentially improved bioavailability for capture by target tissues. However, benefits in terms of MP augmentation and /or improved visual performance were not realised over the 8-week study period, and a study of greater duration will be required to address these questions.